2018
DOI: 10.1186/s13195-018-0455-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Alzheimer’s disease: consequence for drug trials?

Abstract: BackgroundAlzheimer’s disease is a heterogenous disorder with multiple phenotypes and genotypes, although they eventually converge to a final common clinicopathological endpoint. However, Alzheimer’s disease drug trials do not account for the heterogeneity of the disease in trial design, impeding development of effective drugs.DiscussionAlzheimer’s disease drug trials commonly have wide inclusion criteria that subsume multiple subtypes of the condition, with varying genotypes, phenotypes, and clinical courses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 15 publications
0
66
0
1
Order By: Relevance
“…The heterogeneous nature of AD ( 32 ), as a complex neurodegenerative disease affecting multiple biological pathways and processes during onset and progression ( 33 ), represents one major hurdle for AD drug discovery and development. Another hurdle, but simultaneously an opportunity, includes the length of time over which AD develops.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous nature of AD ( 32 ), as a complex neurodegenerative disease affecting multiple biological pathways and processes during onset and progression ( 33 ), represents one major hurdle for AD drug discovery and development. Another hurdle, but simultaneously an opportunity, includes the length of time over which AD develops.…”
Section: Discussionmentioning
confidence: 99%
“…The implication is therefore that stratification on MBI symptoms enriches samples for individuals with preclinical or prodromal disease, creating a more etiologically homogenous sample. Deeper phenotyping including fluid imaging and longitudinal follow up with detailed neuropsychology and clinical outcomes will be required to confirm this hypothesis, which could have important implications for clinical trials where cohort heterogeneity has been identified as a major concern [44].…”
Section: Discussionmentioning
confidence: 99%
“…Gene editing techniques are increasingly used in drug discovery research, [ 302 ], particularly when the genetic cause(s) of disease is known. However, with the recognition that late-life sporadic neurodegenerative diseases frequently have more than one contributing pathology, identifying a single molecular therapeutic target whose manipulation is efficacious in all affected individuals may not be straightforward [ 303 ]. Additionally, and as highlighted in previous sections, given the diverse roles of tau in the human brain, complete MAPT knockdown has been approached cautiously.…”
Section: Tau-directed Therapeuticsmentioning
confidence: 99%